Hypercholesterolemia Abrogates Remote Ischemic Preconditioning-Induced Cardioprotection: Role of Reperfusion Injury Salvage Kinase Signals. Issue 3 (March 2017) - Ma, Lei-Lei; Kong, Fei-Juan; Guo, Jun-Jie; Zhu, Jian-Bing; Shi, Hong-Tao; Li, Yang; Sun, Ren-Hua; Ge, Jun-Bo
Abstract : ABSTRACT: Remote ischemic preconditioning (RIPC) is one of the most powerful intrinsic cardioprotective strategies discovered so far and experimental data indicate that comorbidity may interfere with the protection by RIPC. Therefore, we investigate whether RIPC-induced cardioprotection was intact in hypercholesterolemic rat hearts exposed to ischemia reperfusion in vivo . Normal or hypercholesterolemic rat hearts were exposed to 30 min of ischemia and 2 h of reperfusion, with or without RIPC, PI3K inhibitor wortmannin, MEK-ERK1/2 inhibitor PD98059, GSK3β inhibitor SB216763. Infarct size, apoptosis, MG53, PI3K-p85, p-Akt, p-ERK1/2, p-GSK3β, and cleaved Caspase-3 were determined. RIPC reduced infarct size, limited cardiomyocyte apoptosis following IR that was blocked by wortmannin but not PD98059. RIPC triggered unique cardioprotective signaling including MG53, phosphorylation of Akt, and glycogen synthase kinase-3ß (GSK3β) in concert with reduced proapoptotic active caspase-3. In contrast, RIPC failed to reduce myocardial necrosis and apoptosis as well as to increase the phosphorylated Akt and GSK3β in hypercholestorolemic myocardium. Importantly, we found that inhibition of GSK with SB216763 reduced myocardial infarct size in healthy and hypercholesterolemic hearts, but no additional cardioprotective effect was achieved when combined with RIPC. Our results suggest that acute GSK3β inhibition may provide a novel therapeutic strategy for hypercholesterolemic patients during acute myocardial infarction, whereas RIPC is less effective due to signaling events that adversely affect GSK3β. Abstract : Supplemental Digital Content is available in the text